Factors Associated with the level of Knowledge about the Management of Traumatic Brain Injury in Health Personnel of a Hospital in Northern Peru - Anthony Mezones Vargas, Danai Valladares Garrido, Mario J. Valladares-Garrido, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To identify the factors associated with the level of knowledge about the management of traumatic brain injury (TBI) in health personnel of the emergency service of a hospital in northern Peru. Materials and methods: A prospective analytical cross-sectional study was carried out on physicians from the emergency service of Hospital Santa Rosa, Piura, using a validated instrument. The factors associated with the level of theoretical and practical knowledge about the management of head trauma were identified. Prevalence ratios and 95% confidence intervals were estimated. P-values ​​less than 0.05 were reported. Results: Of a total of 72 participants, it was found that 55.6% were male, 48.6% were specialist doctors, and 51.4% worked in the surgery emergency service. 61.1% (44) presented a high level of knowledge in theoretical and practical aspects while 38.9% (28) obtained a low level of knowledge. The factors positively associated with a higher frequency of theoretical-practical knowledge about TBI were having completed a master's degree or doctorate (PR=2.56), working in the Surgery service (PR=1.66), presenting previous training on TBI (PR=1.37), and manage more than 5 cases of TBI in the emergency during the last 2 weeks (PR=2.20). Conclusion: The level of knowledge in theoretical-practical aspects in TBI was high and this was associated with having a master's degree or doctorate, presenting previous training on TBI, working in the emergency medicine service and managing more than 10 cases of TBI in the emergency during the last 2 weeks.